Feasibility Analysis of Circuit Game Model to Develop Basic Locomotor Skills of Lower Grade Students - Yudha, Rivo Panji; Nurfida, Nurfida (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research aims to evaluate the feasibility of the circuit game model in enhancing the basic locomotor skills of lower-grade students at SD Negeri 1 Labalawa, Waborobo Village. The method employed is a quasi-experimental design with a pretest-posttest format. The sample consists of 73 students from grades 1 to 3, selected purposively. The intervention was conducted over eight weeks with two training sessions per week. Data were collected using TGMD-3, observation sheets, and questionnaires. The results indicate a significant improvement in locomotor skills following the intervention (p < 0.05). In conclusion, the circuit game model is effective in enhancing children's basic motor skills and can be integrated into the physical education curriculum. This study provides recommendations for teachers in developing more interactive and enjoyable game-based learning.